Repositioning drugs for inflammatory disease - fishing for new anti-inflammatory agents - Christopher J. Hall; Sophie M. Wicker; An-Tzu Chien; Alisha Tromp; Lisa M. Lawrence; Xueying Sun; Geoffrey W. Krissansen; Kathryn E. Crosier; Philip S. Crosier (The Company of Biologists, 2014)
Inflammation is an important and appropriate host response to infection or injury. However, dysregulation of this response, with resulting persistent or inappropriate inflammation, underlies a broad range of pathological processes, from inflammatory dermatoses to type 2 diabetes and cancer. As such, identifying new drugs to suppress inflammation is an area of intense interest. Despite notable successes, there still exists an unmet need for new effective therapeutic approaches to treat inflammation. Traditional drug discovery, including structure-based drug design, have largely fallen short of satisfying this unmet need. With faster development times and reduced safety and pharmacokinetic uncertainty, drug repositioning - the process of finding new uses for existing drugs - is emerging as an alternative strategy to traditional drug design that promises an improved risk-reward trade-off. Using a zebrafish in vivo neutrophil migration assay, we undertook a drug repositioning screen to identify unknown anti-inflammatory activities for known drugs. By interrogating a library of 1280 approved drugs for their ability to suppress the recruitment of neutrophils to tail fin injury, we identified a number of drugs with significant anti-inflammatory activity that have not previously been characterized as general anti-inflammatories. Importantly, we reveal that the ten most potent repositioned drugs from our zebrafish screen displayed conserved anti-inflammatory activity in a mouse model of skin inflammation (atopic dermatitis). This study provides compelling evidence that exploiting the zebrafish as an in vivo drug repositioning platform holds promise as a strategy to reveal new anti-inflammatory activities for existing drugs.